Understanding Social Welfare Capitalism, Private Property, and the Government’s Duty to Create a Sustainable Environment - Cooley, Dennis R. (Journal of business ethics, 2008)
No one would deny that sustainability is necessary for individual, business, and national survival. How this goal is to be accomplished is a matter of great debate. In this article I will show that the United States and other developed countries have a duty to create sustainable cities, even if that is against a notion of private property rights considered as an absolute. Through eminent domain and regulation, developed countries can fulfill their obligations to current and future generations. To do so, the governments must reject perfectly competitive free market capitalism and the absolute right to private property, and more fully adopt social welfare capitalism as their economic system. The result will be a sustainable society that balances democracy, individual rights and individual flourishing with the community’s flourishing.